2019
DOI: 10.1177/1420326x19841109
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and influential factors of PM2.5 and CO2 in urban rail carriages

Abstract: The promotion of 'Green Transport' has increased the importance of urban rail transit in China. Increased passenger flow and longer travel time have led to increased attention to in-carriage air quality in trains. In this study, CO 2 and PM 2.5 monitoring were conducted in subway train carriages in a city in northern China. The study accounts for a variety of factors both inside and outside of the train carriages, such as passenger volume and exterior environment. The results reveal that good air quality outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Indoor air quality (IAQ) is frequently measured through CO 2. 21 This study in the Philippines showed a negative correlation (-0.519) between household air pollution health risk exposure value and mean temperature anomaly, similar to studies in Korea and Turkey. The study in Korea investigated the relationship of carbon dioxide in kitchens, living rooms, and bedrooms against temperature among apartments in Seoul.…”
Section: Correlation Of Mean Temperature Anomaly With Health Factorssupporting
confidence: 84%
See 2 more Smart Citations
“…Indoor air quality (IAQ) is frequently measured through CO 2. 21 This study in the Philippines showed a negative correlation (-0.519) between household air pollution health risk exposure value and mean temperature anomaly, similar to studies in Korea and Turkey. The study in Korea investigated the relationship of carbon dioxide in kitchens, living rooms, and bedrooms against temperature among apartments in Seoul.…”
Section: Correlation Of Mean Temperature Anomaly With Health Factorssupporting
confidence: 84%
“…IAQ is frequently measured through CO 2 . 21 The negative correlation of CO 2 and household air pollution health risk exposure value prevalence may be confounded by temperature and ventilation, as seen in the study of Yun et al (2020) and Argunhan and Aci (2018). 22,23 The study results showed that global carbon dioxide measurements negatively correlated to malaria incidence and NTD in the Philippines.…”
Section: Correlation Of Global Co 2 Levels With Health Factorsmentioning
confidence: 85%
See 1 more Smart Citation
“…Through the pre‐debugging program, the robot can walk and avoid obstacles. With the development of artificial intelligence and pattern recognition technology, the use of human motion control robots to achieve HCI has become a hot topic 27,28 . The research of human body motion recognition technology has set off an upsurge at home and abroad.…”
Section: Interactive Animation Creation Based On Artificial Intellige...mentioning
confidence: 99%
“…This, however, consumes a considerable amount of energy, [131] with the result that manufacturers and operators tend to recirculate most of the air and minimise the amount of 'fresh' outdoor air that is supplied to the carriages. [132] CO2 concentrations >1 800 ppm [132][133][134] and as high as 5 525 ppm [135] have been recorded on urban railway carriages during peak periods (CO2 concentrations in well-ventilated spaces are generally <1 000 ppm). [19,31] This suggests that during periods of high occupancy, ventilation rates in passenger carriages are frequently inadequate to protect passengers from far-field SARS-CoV-2 transmission.…”
Section: Scenariomentioning
confidence: 99%